Feasibility of Identifying Acute Nontraumatic Intracerebral Hemorrhage Events Using Diagnostic Coding Among Veterans with Mild Cognitive Impairment or Alzheimer’s Dementia - Dan Berlowitz; Ying Wang; Joel Reisman; Donald Miller; Peter J. Morin; Vanesa Carlota Andreu Arasa; Brant Mittler; Raymond Zhang; Amir Abbas Tahami Monfared; Michael Irizarry; Quanwu Zhang; Weiming Xia (Neurology and Therapy)
Abstract Introduction Based on manual review of clinical notes of using the International Classification of Diseases, Tenth Revision coding, we evaluated the feasibility and validity for monitoring, recording, and reporting intracerebral hemorrhage (ICH) events in patients with all-cause mild cognitive impairment or Alzheimer’s dementia including, but not limited to, patients eligible for anti-amyloid therapy. Methods Principal and first-position hospital discharge codes for ICH events for 200 patients were identified from the Veterans Affairs Health System structured administrative database. Clinician manual review of discharge summary notes assessed and confirmed the presence of coded events. Available documentation of bleed locations was further reviewed, and the extent of event adjudication for potential etiology was assessed. Additionally, 25 acute ICH cases were randomly identified by reviewing discharge notes to confirm corresponding diagnostic code-based reporting. Results Of the 200 identified patients, 161 with acute ICH events were confirmed, resulting in a positive predictive value (PPV) of 80.5% for ICH event presence identified by diagnostic coding. Bleed locations were described for 151 of 161 patients with confirmed events. Of 110 cases whose diagnostic codes indicated an event location, 79 had location descriptions in discharge summaries that were consistent with the coding (PPV = 71.8%). Possible etiology was described in 56/161 patients’ discharge summaries. Among the 25 acute ICH cases identified from discharge notes, 8 had corresponding ICH diagnostic codes. Conclusion This study supports the feasibility and validity of the ICD-10 coding system for monitoring, recording, and reporting ICH event presence. When location is specified in the codes, the ICD-10 coding has an acceptable PPV. Overall, the current diagnostic coding system provides a reasonable framework for initial reporting and may allow for only limited inference of etiology such as differentiating nontraumatic versus traumatic events. Coding accuracy for ICH can be expected to further improve with the availability of guidelines, training, and standardization across clinical practices.